The Effect of Environmental Conditions on the Alkaloid andFlavonoid Content of Basil Leaves (Ocimum basilicum L)Growing in Kandangan Village - Salma, Thania Dita; Na’imah, Janatun; Yunitasari, Norainny (Universitas Negeri Semarang, 2024)
Basil leaves have long been used as fresh vegetables. Basil leaves are used to eliminate odors and can also be used as antiseptics. Each plant can produce primary and secondary metabolites. The production of these metabolites is influenced by environmental conditions. Kandangan Village is one of the villages in Gresik Regency which has a relatively hot temperature and many industries are located around it. The purpose of this study was to determine the results of phytochemical screening tests for the presence of alkaloid and flavonoid compounds in basil leaves growing in Kandangan Village. This type of research is experimental research. Basil leaf samples were obtained from Kandangan Village. The extraction method used was maceration using 96% ethanol solvent. The test for the presence of alkaloids used the Dragendroff test method and the Mayer test. The test for the presence of flavonoids used the Wilstater test method and the Bate Smite-Metcalfe test. The results of this study indicate that basil leaves growing in Kandangan Village are positive for the presence of flavonoids with a color change to yellow for the Wilstater test and a color change to red in the Bate Smite-Metcalfe test. However, the test for the presence of alkaloids showed negative results because there was no formation of orange to red deposits for the Dragendroff test and yellowish white deposits for the Mayer test.